2011
DOI: 10.1111/j.1523-5378.2011.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Helicobacter pylori Eradication on Gastroesophageal Reflux Disease

Abstract: H. pylori eradication does not aggravate the clinical outcomes in terms of short-term and long-term posteradication occurrence of GERD. There is no association between H. pylori eradication and the development of GERD in the patients with different diseases, even those with GERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 24 publications
0
38
0
1
Order By: Relevance
“…However, the short follow-up after eradication may account for the discrepancy between studies. HP eradication does not seem to exacerbate the disease in patients with GORD, thus HP infection in GORD patients may be eradicated (17). Further supporting HP eradication in GORD patients is the need for long-term proton pump inhibitor (PPI) therapy that seems to be associated with an increased risk of developing gastric precancerous conditions, such as corpus atrophic gastritis (18,19).…”
Section: Hp and Gastro-oesophageal Reflux Diseasementioning
confidence: 98%
“…However, the short follow-up after eradication may account for the discrepancy between studies. HP eradication does not seem to exacerbate the disease in patients with GORD, thus HP infection in GORD patients may be eradicated (17). Further supporting HP eradication in GORD patients is the need for long-term proton pump inhibitor (PPI) therapy that seems to be associated with an increased risk of developing gastric precancerous conditions, such as corpus atrophic gastritis (18,19).…”
Section: Hp and Gastro-oesophageal Reflux Diseasementioning
confidence: 98%
“…Fetal considerations include the preservation of adequate maternal oxygenation and blood pressure to allow optimal placental perfusion. Only a few studies have been published on the safety of endoscopy during pregnancy but all showed that gastroscopy and colonoscopy are not associated with adverse outcomes 46 49 133. Where therapeutic intervention is necessary, endoscopy offers a relatively safe alternative to radiological or surgical intervention 34 35 134–138…”
Section: Liver Disease During Pregnancymentioning
confidence: 99%
“…By the way, other studies evaluating the same relation actually produced inconsistent results [75]. A systematic review by Qian et al [76] was aimed to evaluate whether the eradication of HP would worsen or improve GERD, both from the clinical (heartburn, acid regurgitation) and endoscopical (erosive esophagitis) point of view. The 11 articles included in this met-analysis showed no significant difference between patients with HP eradicated and those with persistent infection.…”
Section: H Pylori Infection and Diseases Of The Upper Gastrointesmentioning
confidence: 99%